Linking Sustainability and Happiness Theoretical and Applied Perspectives - Cloutier, Scott; El-Sayed, Sara.; Ross, Allison; Weaver, Melanie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book offers critical discussion, constructive insights and informed guidance for future research and applied work that can move us closer towards a sustainable society. This is the first comprehensive edited book linking sustainability and happiness. By doing so, it frames modern society$1 (Bs pursuit of happiness as the ultimate wicked problem challenging sustainable life on earth. Chapters in the book focus on topics such as food systems, neighbourhood developments, project facilitated gathering and dialogue, beauty, and the happiness movement as an alternative to GDP. This book is of great importance to both academics and practitioners working at the intersection of sustainability and happiness. .s
Part 1: Introduction -- Part 2: Theoretical Perspectives -- Chapter 1. Beauty and Happiness (John de Graaf) -- Chapter 2. Sustainable Happiness (Catherine O$1 (BBrien) -- Chapter 3. Is Happiness Sustainable? (Sonja Lyubomirsky) -- Chapter 4. The Sustainability and Happiness Hypothesis (Jonathan Haidt) -- Chapter 5. Sustainability and Happiness: A Spiritual Perspective (M. Joshanloo) -- Chapter 6. Sustainability and Happiness: A Biological Perspective (M. Angilletta) -- Part 3: Applied Perspectives/Case Studies -- Chapter 7. The Sustainability and Happiness Research Lab (S. Cloutier) -- Chapter 8. Shifting Societal Happiness (Meik Wiking) -- Chapter 9. The Happy City through Transformative Urban Design (Charles Montgomery) -- Chapter 10. Bristol as the Happy City (Liz Zeidler) -- Chapter 11. Promoting Happiness as a Sustainable Alternative to GDP (Laura Musikanski) -- Part 4: Outro as a summary of presented works -- Reference.s
Keywords: Quality of life; Environmental sciences$1 (BSocial aspects.s; Positive psychology; Quality of Life Research; Environmental Social Sciences; Positive Psychology; Happiness; Sustainability -- Psychological aspects; Sustainable development -- Psychological aspects; Well-being